Depredation influences anglers’ perceptions on coastal shark management and conservation in the United States Gulf of Mexico - Prasky, Evan Gerald; Drymon, J. Marcus; Karnauskas, Mandy; Anderson, Alena Q.; Gibbs, Sarah L.; Grabowski, Jonathan H.; Jargowsky, Amanda E.; McAree, Danielle M.; Osowski, Ana R.; Swinea, Savannah H.; Scyphers, Steven B. (Frontiers in Conservation Science, 2023)
Overfishing, habitat degradation, and climate change have caused declines in shark populations throughout the world’s oceans. However, in the United States Gulf of Mexico (GoM), populations of several coastal shark species are starting to stabilize following decades of successful regulations and enforcement. The stabilization of coastal shark populations, coupled with increases in recreational fishing effort, has the potential to escalate human-wildlife interactions. The most often reported conflict is shark depredation, the partial or complete removal of a hooked species by a shark. Reported increases in shark depredation within the last several years have begun to erode angler support for shark conservation, potentially undermining decades of previous work. To address these concerns, we implemented a GoM-wide online survey to characterize the impact of depredation on recreational reef fish anglers’ fishing satisfaction and perceptions of shark management and conservation. Our results revealed that most recreational anglers in the GoM have witnessed depredation but have not changed their fishing behaviors. In contrast, anglers’ viewpoints on managing shark populations were split between reducing population sizes and maintaining current population levels. As coastal shark populations in the GoM continue to recover, shark depredation is likely to increase. Consequently, efforts to characterize anglers’ satisfaction and perceptions are a critical component of future shark conservation initiatives.